Analisis Implementasi Bauran Promosi pada Unit Percetakan Al-Qur'an Kementerian Agama Republik - Komalasari; Sudarijati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to analyze the implementation of promotional mix strategies at the Al-Qur’an Printing Unit (UPQ) of the Ministry of Religious Affairs of the Republic of Indonesia and identify the obstacles faced in achieving revenue targets. The research method used is descriptive qualitative through field observations, documentation, and semi-structured interviews. Informants were selected via purposive sampling, consisting of four key management and marketing staff who hold operational authority. Data analysis followed the interactive model of Miles, Huberman, and Saldaña (data condensation, data display, and conclusion drawing). The results of the study show that UPQ’s revenue realization in 2024 only reached 94,56% of the target. The primary structural factors hindering this achievement were a limited budget for operational promotion and a lack of expert marketing staff, which led to an over-reliance on social media and restricted exhibitions. This study recommends optimizing electronic advertising with informative content, developing print media for religious events, and implementing tactical sales promotion strategies such as holiday discounts and product sampling. The theoretical contribution of this research lies in conceptualizing an Integrated Marketing Communication (IMC) framework specifically adapted for government-owned religious institutions with dual public service and semi-commercial functions, thereby bridging the literature gap between private and public sector marketing dynamics.